2011
DOI: 10.3171/2011.1.spine10310
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting the feasibility of monitoring lower-limb muscle motor evoked potentials in patients undergoing excision of spinal cord tumors

Abstract: Object This prospective study on intraoperative muscle motor evoked potentials (MMEPs) from lower-limb muscles in patients undergoing surgery for spinal cord tumors was performed to: 1) determine preoperative clinical features that could predict successful recording of lower-limb MMEPs; 2) determine the muscle in the lower limb from which MMEPs could be most consistently obtained; 3) assess the need to monitor more than 1 muscle per limb; and 4) determine the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 13 publications
2
22
2
Order By: Relevance
“…Secondly, we did not analyze the preoperative motor weakness of patients with unobtainable baseline MEPs. Indeed, a previous study indicated that successful MEP recordings were possible in only 27.5% patients with an MRC grade 0–3 (Rajshekhar et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we did not analyze the preoperative motor weakness of patients with unobtainable baseline MEPs. Indeed, a previous study indicated that successful MEP recordings were possible in only 27.5% patients with an MRC grade 0–3 (Rajshekhar et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Muscle MEPs (mMEPs) are a reliable technique for monitoring motor pathways. 41,44 Transcranial electrical stimulation with a multipulse technique is used for eliciting mMEPs and includes short trains of 5 square-wave stimuli (single pulse duration 0.5 msec, interstimulus in-terval 4 msec, rate 2 Hz) through corkscrew electrodes placed at C1/C2 (lower limbs) and C3/C4 (upper limbs) scalp sites. The mMEPs are recorded through needle electrodes inserted into the upper-and lower-extremity muscles; they do not require averaging, but they do have wide amplitude and morphological variability.…”
Section: Motor Evoked Potentialsmentioning
confidence: 99%
“…Rajshekhar et al showed that 89% of patients with preoperative Nurick grades of 0–3 provided successful recordings, compared to only 7.1% of patients with preoperative Nurick grades of 4–5. 26) …”
Section: General Remarksmentioning
confidence: 99%